Collaborative governance outcomes and obstacles: Evidence from Portuguese armed forces - Diogo Moreno; Tiago Cruz Gonçalves (Cogent Business & Management, 2021)
The shortage of resources, which threats the accomplishment of the Armed Forces' Missions, has urged them to increase their Branches' integration to improve their efficiency as a whole. However, previous research pinpointed several issues in the Portuguese Armed Forces' (PAF) governance that have threatened the intended integration's efficacy. Therefore, we analyse PAF's governance model at the Military Strategic Planning (MSP) level to understand its suitability to PAF's current and future needs. We extend theoretical understanding of collaborative governance in defence, using a mixed method approach through a case study analysis, conducting structured and semi-structured interviews (15 interviewees), a survey (97 answers), and several document analyses. Participants' sample includes military and civilian personnel working on MSP or financial resources management. The results highlight that PAF's governance model is mostly a classic Public Administration model that is not sufficiently suited to answer its integrative needs. This study identifies the main obstacles of Defence Military Branches' integration and provide theoretical propositions to frame collaborative governance in Public Administration. It also shows evidence to back up the importance of collaborative governance models, supported on interdependent networks, and argue the impact that non-rational factors (such as organizational culture) can have in public entities' governance.
Keywords: H83; H77; H56; H11; 650; collaborative governance; strategic military planning; case study; efficiency; organizational culture